A meta-analysis and systematic review: Success of endoscopic ultrasound guided biliary stenting in patients with inoperable malignant biliary strictures and a failed ERCP. Issue 3 (January 2017) - Moole, Harsha; Bechtold, Matthew L.; Forcione, David; Puli, Srinivas R.
Abstract: Background: In patients with inoperable malignant biliary strictures, endoscopic retrograde cholangiopancreatography (ERCP) guided biliary stenting fails in 5% to 10% patients due to difficult anatomy/inability to cannulate the papilla. Recently, endoscopic ultrasound guided biliary drainage (EUS-BD) has been described. Primary outcomes were to evaluate the biliary drainage success rates with EUS and compare it to percutaneous transhepatic biliary drainage (PTBD). Secondary outcomes were to evaluate overall procedure related complications. Methods: Study selection criteria: Studies evaluating the efficacy of EUS-BD and comparing EUS-BD versus PTBD in inoperable malignant biliary stricture patients with a failed ERCP were included in this analysis. Data collection and extraction: Articles were searched in Medline, PubMed, and Ovid journals. Two authors independently searched and extracted data. The study design was written in accordance to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. Subgroup analyses of prospective studies and EUS-BD versus PTBD were performed. Statistical method: Pooled proportions were calculated using fixed and random effects model. I 2 statistic was used to assess heterogeneity among studies. Results: Initial search identified 846 reference articles, of which 124 were selected and reviewed. Sixteen studies (N = 528) that met the inclusion criteria were included in this analysis. In the pooled patient population, the percentage of patients that had a successful biliary drainage with EUS was 90.91% (95% CI = 88.10–93.38). The proportion of patients that had overall procedure related complications with EUS-PD was 16.46% (95% CI = 13.20–20.01). The pooled odds ratio for successful biliary drainage in EUS-PD versus PTBD group was 3.06 (95% CI = 1.11–8.43). The risk difference for overall procedure related complications in EUS-PD versus PTBD group was −0.21 (95% CI = −0.35 to −0.06). Relative risk for infectious complications and bile leak in EUS-BD versus PTBD was 0.25 (95% CI = 0.07–0.94) and 0.33 (95% CI = 0.12–0.87), respectively. Conclusions: In patients with inoperable malignant biliary strictures who failed an ERCP guided biliary stenting, EUS-BD seems to be an excellent management option and superior to PTBD with higher successful biliary drainage rates and relatively fewer complications.